A diagnostic 'C' saw: the ups and downs of C1q testing. Issue 4 (August 2019) - Gebel, Howard M.; Bray, Robert A.
Abstract : Purpose of review: The present review will focus on recently published data of solid organ allograft recipients reporting that patients with de-novo donor-specific HLA antibodies (DSA) that fix complement in vitro have a significantly higher risk for antibody-mediated rejection (AMR) and/or graft loss compared to patients whose de-novo DSA do not fix complement or patients who present with preexisting complement fixing DSA. Recent findings: HLA DSAs that fix complement in vitro appear to be a key indicator for rejection and failure of kidney, heart, and lung allografts from studies performed around the world. The majority of these studies are population based and retrospective in nature. Although these studies seemingly indicate that in-vitro complement activating DSAs represent a higher clinical risk than noncomplement fixing DSAs, the majority have not accounted for false-negative reactions attributable to the so-called prozone/interference phenomenon. In the limited number of published studies addressing that concern, high mean fluorescence intensity (MFI) value noncomplement fixing DSAs correlate as well as complement fixing DSAs with AMR and graft loss. Combined with the cost of additional testing, these observations bring into question whether there is sufficient clinical applicability to warrant routine testing for complement fixing antibodies. Summary: Complement fixing DSAs are clearly associated with AMR and/or loss of transplanted allografts. However, under appropriate testing conditions, complement fixing capability typically correlates with MFI values of the DSAs. As such, the routine implementation of in-vitro assays to determine whether DSAs fix complement is of questionable value especially when considering additional issues such as cost of testing, logistics, and whether the test results factor into individualized patient care.